Patrouille des frontières nationales et représentations racialisées: Analyse de commentaires en ligne sur les réfugiés syriens au Québec - Forcier, Mathieu (Refuge: Canada’s Journal on Refugees, 2019)
This article analyzes comments published on the Facebook pages of major Quebec media outlets about the Canadian resettlement plan for Syrian refugees in 2015. The study seeks to probe the particular configuration of the normalization of white ethnic majorities’ national belonging under the mode of worry. Five commonplace ideas are identified in the negative discursive framing of the arrival of Syrian refugees: numbers, financial burden, national responsibility, culture, and security. The results show that racialized exclusion can operate without recourse to openly racist language, notably through the representation of the “people” as a victim of multicultural elites.